Tradisi Cuci Kaki sebagai Sarana Komunikasi Budaya: Upaya Menjaga Kearifan Lokal dalam Dinamika Politik Komunitas Adat di Maluku - Solissa, Rivaldo; Salakay, Selvianus (Populis: Jurnal Ilmu Sosial dan Ilmu Politik, 2024)
This article explores the foot-washing tradition (locally known as hobo kadan) as a form of cultural communication within the indigenous community of Leksula Village, Eastern Indonesia. The main objective of this study is to understand the symbolic meanings, social functions, and political relevance of the ritual as it relates to women preparing for marriage, and to assess its role in preserving local wisdom amid the socio-political dynamics of indigenous society. Employing a qualitative ethnographic approach, the research involved participant observation, in-depth interviews with traditional elders, community leaders, and ritual participants, as well as narrative analysis of the cultural practice. The findings reveal that hobo kadan is not merely a ceremonial ritual, but a symbolic act of social and spiritual transition—marking a woman’s passage from her former life into the ideals of married life. The tradition also reflects social legitimacy through the mutual agreement of two families, functioning as a form of public communication to signal that the marriage process will soon take place lawfully and transparently. In the political context of the indigenous community, this practice reinforces social cohesion, affirms traditional authority structures, and symbolizes resistance to the homogenization of external cultures. The novelty of this study lies in its articulation of hobo kadan as a cultural communication tool that actively contributes to the socio-political stability of indigenous communities. This study recommends formal recognition and protection of local cultural practices in development policy, and advocates for the integration of indigenous knowledge systems into the advancement of social and political sciences—particularly in the study of identity politics, symbolic culture, and political communication in indigenous contexts.